2022
DOI: 10.24042/ajpm.v13i1.11711
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hawgent dynamic mathematics software on mathematics achievement: A meta-analysis

Abstract: In recent years, ICT development has greatly affected the education sector. The development has provided many opportunities to innovate and improve the quality of education. Dynamic mathematics software is one of the learning media that is widely used in mathematics lessons. China has always wanted to be innovative by developing Hawgent Dynamic Mathematics software with more features than other dynamic mathematics software. This research aims to determine the effect of Hawgent Dynamic Mathematics software on m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 37 publications
(49 reference statements)
1
5
0
Order By: Relevance
“…This was line to some metaanalysis studies that computer technology-assisted mathematics education significantly enhanced students' mathematics achievement [84,85,87,88]. In addition, a few of meta-analysis studies showed that the utilization of mathematics software in mathematics learning activities significantly enhanced students' mathematics learning outcome [89,91,103]. More specific, some meta-analysis studies found that the utilization of DGS and CAS in geometry and algebra learning significantly cultivated students' geometric and algebraic achievement [81,92,94,104].…”
Section: A the Effect Of Ict-based Or -Assisted Mathematics Learning ...supporting
confidence: 67%
See 4 more Smart Citations
“…This was line to some metaanalysis studies that computer technology-assisted mathematics education significantly enhanced students' mathematics achievement [84,85,87,88]. In addition, a few of meta-analysis studies showed that the utilization of mathematics software in mathematics learning activities significantly enhanced students' mathematics learning outcome [89,91,103]. More specific, some meta-analysis studies found that the utilization of DGS and CAS in geometry and algebra learning significantly cultivated students' geometric and algebraic achievement [81,92,94,104].…”
Section: A the Effect Of Ict-based Or -Assisted Mathematics Learning ...supporting
confidence: 67%
“…Some previous meta-analysis studies also revealed that computer technology-assisted mathematics learning had moderate positive effect on students' mathematics achievement [9,10,13,86]. Additionally, Li et al [89] found that the use of mathematics software in mathematics learning activities had moderate positive effect on students' mathematics learning outcome. Even, a few meta-analysis studies found that mathematics software-assisted mathematics learning had strong positive effect on students' mathematics learning outcome [91,103].…”
Section: A the Effect Of Ict-based Or -Assisted Mathematics Learning ...mentioning
confidence: 93%
See 3 more Smart Citations